Neural network and fuzzy logic to track maximum power point in photovoltaic system - N. Drir; L. Barazane; M. Loudini (Revue des Énergies Renouvelables, 2014)
The output characteristics of photovoltaic systems are nonlinear and change with variations of temperature and irradiation, so we need a controller named maximum power point tracker MPPT to extract the maximum power at the terminal of photovoltaic generator. This study explores two intelligent controller based on a neural networks and fuzzy logic to track this point. These both controllers have prove, by their results, a good tracking of the MPPT compare with the other methods which are proposed up to now.